EFEKTIVITAS MEKANISME PENGISIAN JABATAN STRUKTURAL BERBASIS SISTEM MERIT DI PEMERINTAH KABUPATEN POLEWALI MANDAR - Andi M Ferian Maha Putra P; Yusriah Amaliah (Jurnal SUTASOMA (Science Teknologi Sosial Humaniora), 2025)
The appointment of structural positions in local government is essential for achieving professional and accountable human resource governance. However, this process often faces challenges related to employee competency and limited supporting facilities. This study aims to analyze the effectiveness of the structural position appointment mechanism in Polewali Mandar Regency based on the merit system principles mandated in Regulation of the Minister of Administrative and Bureaucratic Reform Number 15 of 2019. This research employs a qualitative approach through interviews, observations, and documentation review. The findings indicate that the appointment process has followed formal procedures, including administrative screening, track record verification, managerial assessment, and field competency tests. Nevertheless, its effectiveness is hindered by limited employee competence in personnel management, mismatches between technical expertise and assigned positions, and the absence of an adequate assessment centre. The study recommends enhancing personnel capacity through competency-based training, strengthening consistent implementation of the merit system, and providing standardized assessment facilities. These improvements are expected to increase transparency, objectivity, and the overall quality of structural position appointments in local government.